2021
DOI: 10.47176/mjiri.35.29
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of selected decision tree algorithms for COVID-19 diagnosis using routine clinical data

Abstract: Background: The novel 2019 Coronavirus disease (COVID-19) poses a great threat to global public health and the economy. The earlier detection of COVID-19 is the key to its treatment and mitigating the transmission of the virus. Given that Machine Learning (ML) could be potentially useful in COVID-19 identification, we compared 7 decision tree (DT) algorithms to select the best clinical diagnostic model. Methods: A hospital-based retrospective dataset was used to train the sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…According to the C4.5 decision tree, "contact with a person who has COVID-19" was determined as the first divider in identifying the infected person. Among the research that have been done with the aim of diagnosing COVID-19 based on ML algorithms in Iran, we can mention the research of Shanbehzadeh M et al ( 37 ). In order to select the best detection model, they compared 7 decision tree algorithms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the C4.5 decision tree, "contact with a person who has COVID-19" was determined as the first divider in identifying the infected person. Among the research that have been done with the aim of diagnosing COVID-19 based on ML algorithms in Iran, we can mention the research of Shanbehzadeh M et al ( 37 ). In order to select the best detection model, they compared 7 decision tree algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…But in Shanbehzadeh M's research, "the lung lesion existence" is the most important factor identified. One of the strengths of our research compared to( 37 )is high volume dataset. Also, since our dataset is related to a province (Fars province), our results have more integrity than Shanbehzadeh M's research, which used only the data from one hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Brinati et al [9] proposed ML model to detect the infection of COVID-19 based on routine blood, with accuracies ranging from 82 to 86%. Some studies have explored robust ML models based on patients' conventional clinical data, disease history, epidemiological factors and other physiological characteristics to diagnose covid-19 [10,11]. A study investigated the value of Chest-tomography (CT) images for covid-19 severity assessment and clinical outcome prediction [12].…”
Section: Introductionmentioning
confidence: 99%
“…Decision trees are efficient and reliable decision‐making algorithms, because they are characterized by high classification accuracy and simple visualization of collected data. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…The input variables can be continuous and categorical, and based on them, the final classification is made. Decision trees are efficient and reliable decision‐making algorithms, because they are characterized by high classification accuracy and simple visualization of collected data 10,11 …”
Section: Introductionmentioning
confidence: 99%